Formulasi Krim Tipe A/M dari Ekstrak Rimpang Cyperus rotundus L. Untuk Pengobatan Nyeri Sendi - Yenti, Revi; Rahim, Farida; Firmansyah, Firmansyah; Syayuni, Aziza (Jurnal Farmasi Indonesia, 2016)
The purpose of this study were to formulate and determined the effect of the cream type W/O ethanolic extract of the rhizome of teki (Cyperus rotundus L) as join paint medicine. This research were uses three formulas (F1, F2,and F3) with concentration 3%, 5% and 7% of ethanol extract. The formulas were evaluated for their organoleptic, homogenity, cream type, pH, washability, stability of temperature, particle size distribution, skin irritation. The test of curing the join pain effect has done to the white male rats which induced by AgNO 3 1% as the pain inductor via intra articular. The parameter that we have seen is amount of sweaking in 30 minutes, an hour, 1,2,4,6 and 8 hours. The cream formula of ethanol extract of the rhizome of teki was consistant in allconcentrations. Based on the result of statistical, group V (Formula 3) was gave faster reaction in fourth time of observation than other formula.